Гендерна когнітивна та поведінкова асиметрія в перекладі - Засєкін, Сергій Васильович; Засєкіна, Лариса (Lesya Ukrainka Eastern European National University, 2016)
The present paper outlines results of a psycholinguistic study of gender cognitive and behavioral tendencies reflected in a specially compiled bilingual corpus of translated and original texts of fiction. The authors attempt to show how gender can affect translator’s choices in English - Ukrainian literary translation. A special focus is on S-universals (Chesterman, 2011), since their study gives a direct access to translators' mental operations. Explication, simplification on the lexical and syntactic levels, the use of more frequent lexis in the target texts, lack of repetitions, avoidance of culture-bound terms, standardizing, and convergence belong to a group of the main gender-dependent translation S-universals. Among the most typical findings of the research are women’s better flexibility in the translation viewed as a metacognitive universal of their “global” thinking, i.e. a synthetic cognitive style. Female translators have shown higher indices of target text lexical density, explicitation and nominalization. By contrast, male translators tend to avoid nominalizations, being more accurate when reproducing certain source text units, thereby opting for a semantic method (Newmark, 1988) of translation. This universal strategy manifests their analytical cognitive style. When translating the status-asymmetrical conversations in the source text, where fictional characters perform socially marked or blurred roles, men aim at retaining negative politeness in their target language versions. Статтю присвячено вивченню впливу чинника статі мовного посередника на застосовувані ним пріоритетні стратегії під час створення цільового тексту. Емпіричним матеріалом дослідження слугували тексти англомовної художньої прози та їхні українські переклади у виконанні чоловіків та жінок. Застосований у праці психолінгвістичний підхід до аналізу двомовного корпусу дав змогу встановити деякі ‘S-універсалії’ (Chesterman, 2011) вибору різностатевими посередниками тих чи тих мовних структур, що дає підстави погодитися з іншими дослідниками в питанні існування значущих відмінностей у гендерних пріоритетах структурування перекладного дискурсу. Серед найпомітніших “жіночих” універсалій в перекладі українською – метакогнітивна гнучкість, що кваліфікуємо як синтетичний когнітивний стиль. Крім того, простежено застосування перекладачками стратегії статусної нейтралізації в діалозі між персонажами під час відтворення статусно-маркованих і дифузних ситуацій; вищі показники лексичного розмаїття, експліцитації й номіналізації, ніж у цільових версіях перекладачів чоловічої статі. Останні виявляють більшу обережність у перекладі, вдаючись до ‘семантичного методу’ (Newmark, 1988) перекладу, виявляючи відтак аналітичний когнітивний стиль поведінки, а також демонструючи стратегію негативної ввічливості під час відтворення діалогів персонажів у статусно-маркованих і статусно-дифузних комунікативних ситуаціях.
Keywords: гендер; перекладач; перекладачка; когнітивна та поведінкова асиметрія; психолінгвістика; перекладацька універсалія; gender; male translator; female translator; cognitive and behavioral asymmetry; psycholinguistics; translation universal